DETERMINAN PERILAKU ETIS ENTREPRENEUR DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Sugiharti, Sugiharti (STIE Totalwin Semarang, 2013)
This paper reviews and extends the literature on entrepreneurs ethical behavior. Building on previous ethical decision making models, we argue that the nature of both the entrepreneur and the entrepreneurship context warrant additional theorizing within the ethics literature. We propose that entrepreneurs face unique internal and external drivers of ethical behavior. Likewise, in the course of engaging in entrepreneurial activities, the entrepreneurs higher accountability and concern for reputation may lead to relativelyÂ higher ethical conduct, while the increased uncertainty may countervail these pressures. We discuss the implications of these tensions and future directions for research.